Spirit ”Kembali Kepada Al-Qur’an dan Sunnah” di Era Disrupsi dalam Muhammadiyah Perspektif Amin Abdullah - Ahmad Qoiman (Jurnal Studi Hadis Nusantara, 2021)
The philosophical foundation “returned to the Qur’an and Sunnah” is always applied in Ijtihad activities to produce updated products in Islam in the community. This article discusses how spirit Ruju ‘ila Al-Qur’an wa as-sunnah in Muhammadiyah in the perspective of Amin Abdullah is related to the era of disruption that is happening. Through literature studies, the results of the study stated that Amin Abdullah confirmed the concept of “returning to the Qur’an and Sunnah” held by Muhammadiyah was right. The aspect that needs to be criticized and excavated in advancing Muhammadiyah is the historicity of the religious Muslim community, not the normativity of the source of his religion. The application of the Fresh Ijtihad method using interdisciplinary, multidisciplinary, and transdisciplinary approaches is needed if Islam wants to continue to exist amid an age that is experiencing disruption. One of the concrete steps according to sunglasses Amin Abdullah is by reforming the Ihsan’s idea that the Prophet had ever explained when discussing with Jibril. Ihsan can form individual piety that needs to continue to be developed in groups of groups, organizations, and institutions. Because, when until the level of a group of individuals forming a group of piety, individuals fell. As if the idea of Ihsan said “You worship Allah as if you see Him, then if you don’t see Him then Allah sees you” does not apply when a person has joined a group. Even though the glory of Western civilization which is currently the world’s Qibla built by good organizational management through revolutionary updates.